Mard-e-Momin - Edited by Abdul Hameed Khan (Lahore Ferozsons Ltd., 1968)
Sheikh ut-Tafseer Hazrat Maulana Molvi Ahmad Ali Sahib ki pak zindagi kay pakeezah halaat.
Include Illustrations.
Urdu Biography.
Keywords: Biography - Islamic -- Biography - Urdu -- Islamic Urdu Biography -- Mard e Momin